A Preformed Binding Interface in the Unbound Ensemble of an Intrinsically Disordered Protein: Evidence from Molecular Simulations - Knott, Michael; Best, Robert B. (PLOS Computational Biology, 2012)
Author Summary While many proteins have a specific ‘native’ conformation, so-called intrinsically disordered proteins (IDPs) adopt many different conformations in rapid succession—a characteristic that may be advantageous for rapid binding and promiscuous association. However, this characteristic also makes it very hard to make experimental measurements over times that are short enough to see changes of conformation. In this work, we use the results of a large-scale molecular simulation to explore conformations of NCBD, which is an IDP that adopts specific conformations when it binds either of two other proteins (ACTR and IRF-3). Our results point to the following hypothesis: to help NCBD bind ACTR, those parts of NCBD that make contact with it in the bound conformation are biased towards that conformation, even in the absence of ACTR. Other parts of NCBD tend to avoid the ACTR-bound conformation, to help ensure that NCBD is disordered when unbound.